PENERAPAN KESELAMATAN DAN KESEHATAN KERJA BALAWISTA DI PANTAI KUTA - Satwika Wiguna Kusuma; Ida Bagus Suryawan (Program Studi Sarjana Pariwisata, Fakultas Pariwisata, Universitas Udayana, 2016)
Abstract Kuta beach is one of the most visited places in Bali, it offer a great beach with a perfect wave to surf and become a number one spot for any tourist who come to Bali for surfing. With that being said the accident rate of water related accident in the area is very high, to manage the risk and ensuring the safety of the area Gede Berata a Balinese partnering with two Australian Kevin Weldon and Alan B Welpton founding The Indonesian Surf Life Saving Association/ Badan Penyelamat Wisata Tirta or more known as Balawista. This job require a very high standard of commitment, not only a competent staff but also need a sufficient equipment to help the rescue activity, it also require a high standard of operation procedure to ensure that the rescue are done in a safe and efficient manner to ensure the safety for both of the victims and rescuers. The goals of this research are to know how far Balawista implement health and safety procedure when doing daily operation, and what are the other factors that impacting the performance of Balawista. The data are collected using an observation method and in-depth interview and using purpose sampling method, data analytic method using qualitative descriptive. With this paper writer hope that Balawista will be able to do their job professionally by implementing health and safety procedure considering the high importance of their job and by doing that they will be able to increase the safety for both of the victims and rescuers.